SKILLED AT WRITING CHILDREN'S STORIES WITH SMARTPHONE APPLICATION (Case Study in Paud Terpadu Bunda Tami Tasikmalaya) - Ayi Maulida (IKIP Siliwangi Bandung, 2018)
This article is based on the research that aims to improve the skills of teachers in writing stories using the application of Art Filters and Pictsay Pro on smartphone as a helper for teachers to make stories to PAUD students. The research method is done by using Research and Development approach (R & D), i.e. research that is followed up by producing the product and testing the effectiveness of the product. This research involves teachers in PAUD TERPADU BUNDA TAMI and also the students. The research procedure consists of two stages, the first is introduction and the second is model development. Data were collected by using observation; interview, documentation, questionnaires and expert validation test, and the results were analyzed using qualitative analysis techniques. Research shows that there is an increase in teachers' skills in writing the story, because the existence of these products provide new ideas and to develop a story with regard to the principles in PAUD development, such as holistic, contextual, meaningful, and fun. Student activeness in story learning also increased, this is because children can be the subject of the story so they feel enthusiastic and has a high interest to listening, asking and telling themselves in an event or somewhere according to the theme of the learning process.Keywords: Writing, Writing children's story, Smartphone Applications